Analysis of the Effectiveness of Implementing Regulations Restricting Smartphone Use as an Effort to Handle Student Behavior - Khaerul Aqbar; Azwar Azwar; Dewi Indriani; Awal Rifai; Mutahharah Mutahharah (Aksara Shofa, 2024)
The use of smartphones in the STIBA Makassar environment has the potential to cause students to tend to behave deviantly, especially in aspects of the Shari'a and its practice. With concerns about this potential, regulations limiting the use of smartphones have been established as an Islamic social control so that guidance in the STIBA Makassar environment can run as expected and be able to direct students to maintain their behavior in life. This research was conducted with the aim of analyzing the effectiveness of regulations limiting the use of smartphones in controlling student behavior at STIBA Makassar. This research uses primary data through questionnaires and a quantitative approach through descriptive statistics techniques and difference tests (paired sample t-test). The results of the research show that, in general, there has been a decrease in the frequency of smartphone use for deviant behavior. This can also be seen in the increase in the frequency level of